Evaluasi Kebijakan Sistem Zonasi Dalam Penerimaan Peserta Didik Baru (PPDB) di SMPN Kabupaten Tanah Datar - Muhammad Jamil; Suswati Hendriani; Devy Aisyah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study is about the acceptance of new students (PPDB) at SMPN Tanah Datar by using a zoning system. As for the goals of this study is to find out how it is implemented, as well as the supporting and inhibiting factors in PPDB by using the zoning system at SMPN Tanah Datar Regency. This study uses qualitative methods with phenomenological types. The research instrument is the researcher himself and is added with notebooks, recording devices, and other documents as supporters. Sources of data were obtained from principals, teachers, parent and student at 7 SMPN Tanah Datar Regency. data collection using observation techniques, interviews and documentation. to check the validity of the data using the triangulation method and then analyzed using the Miles and Hubermen model consisting of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that in the implementation of the zoning system policy in the acceptance of new students (PPDB) at SMPN Tanah Datar for 3 years, there were several problems encountered in the field such as zone mapping by the local government which was not yet accurate, the quota set was not in accordance with the needs. schools, regulations that are not yet firm so that there are still schools that violate the zoning provisions in the PPDB, there is still a lack of socialization to the community and the motivation and learning achievement of students / wi has decreased. The conclusion in this study is that the government as a stakeholder in education needs to evaluate especially in education policies in order to assess and measure whether the zoning system in PPDB has been implemented properly or not, what needs to be improved and addressed and can provide inputs. input so that the zoning system policy in this PPDB will be even better next time.